DETERMINAN BANTUAN LANGSUNG TUNAI (BLT) DI MASA PANDEMI COVID – 19 DI MODERASI OLEH PENDUDUK MISKIN ( STUDI KASUS DI KECAMATAN SEI BINGAI ) - Sri Ertina; Afrah Junita; Nasrul Kahfi Lubis (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2023)
With this research we can find out the effect of accountability on the management and allocation of village funds on direct cash assistance during the Covid-19 pandemic with the poor as moderators. Purposive sampling technique was used in this study, this technique is sampling with certain considerations and criteria, while the method used in this study is a quantitative method with primary and secondary data and data collection is done by questionnaires, interviews and observation. The phenomenon that occurs in this study is the lack of responsibility of village officials in providing direct cash assistance, meaning that the incoming funds are not the same as the outgoing funds and the receipt of the assistance is not on target. This study shows the following results that management accountability has a negative but significant effect on direct cash assistance. Allocation of village funds has a positive and significant effect on direct cash assistance. The poor have a significant and positive effect on direct cash assistance. The poor can moderate the management Accountability for Direct Aid. Poor residents can moderate the allocation of village funds to direct cash assistance. Poor residents can moderate Accountability for management and allocation of village funds simultaneously affects direct cash assistance in Sei Bingai District